Synthetic Studies Towards Spirocyclic Imine Marine Toxins Using N-Acyl Iminium Ions as Dienophiles in Diels–Alder Reactions - Freeman, Jared L.; Li, Freda F.; Furkert, Daniel P.; Brimble, Margaret A. (Synlett, 2020)
Cyclic imine marine toxins have attracted considerable attention from the synthetic community in the past two decades due to their unique chemical structures and clinically relevant biological activities. This review presents recent efforts of our group in the development of various strategies to efficiently construct the common spirocyclic imine fragments of the cyclic imine toxins. In particular, the use of α,β-unsaturated N-acyl iminium ion dienophiles in Diels–Alder reactions are highlighted, whereby direct access to spirocyclic imine motifs was obtained and important mechanistic details were discovered. Alternative approaches to spirocyclic imine systems involving hydroamination of amino alkynes are also summarized. One such approach led to serendipitous access to N-vinyl amide products, while our most recently reported approach involving an intermolecular Diels–Alder/cross-coupling sequence using novel 2-bromo-1,3-butadienes to access 5,6-spirocyclic imines is also discussed. Additionally, the development of a novel method to construct another challenging motif present in the portimines is also introduced.1 Introduction2 Strategies towards the Spirocyclic Imine Fragment of Cyclic Imine Toxins2.1 Diels–Alder Cycloadditions of α,β-Unsaturated N-Acyl Iminium Dienophiles2.2 Early Studies Using in situ-Generated Iminium Ion Dienophiles2.3 Use of More Stable Iminium Ion Dienophiles for Diels–Alder Reactions2.4 Other Notable Strategies towards Spirocyclic Imines2.5 Recent Efforts towards the 5,6-Spirocyclic Imine Marine Toxin Portimine A2.6 Construction of Another Challenging Motif of Portimine A3 Conclusion and Future Perspectives
Keywords: spiroimines; Diels-Alder reaction; N-acyl iminium ions; Mukaiyama Michael addition; iminium dienophiles